Analysis of Growth and Survival of Kelabau Fish Larvae (Osteochilus melanopleurus) Fed Natural Feeds With Different Feed-Transition Periods - Akmal; Rukmini; Noor Arida Fauzana (International Journal of Science and Environment (IJSE), 2026)
Kelabau fish is a local freshwater fish with high economic value, however, successful seed production is still constrained by high mortality and slow growth during the larval stage. This study aimed to analyze the growth and survival of kelabau fish larvae fed natural feeds with different feed-transition periods. The study was conducted at the Mandiangin Freshwater Aquaculture Center using a completely randomized design (CRD) with four treatments and three replications. The tested treatments consisted of different transition times among natural feeds, namely infusoria, Artemia nauplii, and Moina, for larvae aged two days after hatching during a 15-day rearing period. The observed parameters included absolute length growth, absolute weight growth, and larval survival. The data were analyzed using analysis of variance (ANOVA) at a 95% confidence level, followed by Duncan’s test when significant differences were found. The results showed that different natural-feed transition periods had a significant effect (P < 0.05) on larval length growth, but had no significant effect (P > 0.05) on weight growth or survival. The highest length growth was obtained in treatment A at 8.55 ± 0.34 mm, followed by treatment B at 8.42 ± 0.28 mm, while the lowest value was recorded in treatment D at 7.08 ± 0.13 mm. Weight growth ranged from 0.0161 ± 0.0016 to 0.0179 ± 0.0033 g, and survival ranged from 83.33 ± 3.85% to 95.56 ± 5.09%. Treatment A, consisting of infusoria feeding until day 2 and a combination of infusoria and Artemia nauplii starting on day 3, was the best treatment for improving larval length growth. Therefore, an earlier transition to Artemia nauplii, beginning on day 3 of rearing, is the optimal period to support the growth of kelabau fish larvae without reducing their survival rate.